Respuesta :

Answer:

121

Step-by-step explanation:

This is an arithmetic sequence.

First term  a = -15

Common difference [d] = second term - first term

                                  = -11 - [-15] = -11 + 15 = 4

nth term = a + (n-1) * d

35th term = -15 + (35 - 1) * 4

                = -15 + 34 * 4

                = - 15 + 136

                = 121

TehGOD

Answer:

121 and 257

Step-by-step explanation:

So we would have our equation for arithmetic sequences which is [tex]a_{n} =a_{1} +(n-1)d[/tex] a1 is the first term, n is the term we want to know, and d is the common difference. We would plug in the numbers into the equation so we would get [tex]a_{n} =-15+(35-1)4[/tex]. And if you simplify you would get [tex]a_{n} =121[/tex].

Than for the other one we would do the same thing so you would get [tex]a_{n} = 121+(35-1)4[/tex] and if you simplify you would get [tex]a_{n} =257[/tex].

ACCESS MORE
EDU ACCESS
Universidad de Mexico